Bisphosphonates and breast carcinoma - Allan Lipton (1997)
The skeleton is a common site of breast carcinoma metastasis; 75% of patients with breast carcinoma demonstrate bone metastases at autopsy. The lytic destruction of bone in these patients is due to excessive osteoclastic activity. By reducing osteoclastic activity, bisphosphonates inhibit bone resorption. Initial studies of breast carcinoma patients were performed with clodronate, a first-generation bisphosphonate. Studies with small cohorts suggested reduction of pain, analgesic requirement, and development of hypercalcemia. A larger randomized, double-blind, placebo-controlled trial of oral clodronate 1600 mg/day demonstrated a significant reduction of the combined rate of all morbid skeletal events (significant reduction of the incidence of vertebral fractures, rate of vertebral deformity, and hypercalcemic episodes). Trends were observed that favored clodronate for the treatment of nonvertebral fractures and radiotherapy for relief of bone pain. There was no survival difference between the clodronate and placebo groups (Paterson et al., J Clin Oncol 1993;11:59-65). Pamidronate is a second-generation aminobisphosphonate that is a much more potent inhibitor of osteoclastic activity. Phase II studies again suggested an improvement in many of the skeletal complications of breast carcinoma. Two large Phase III studies have recently been completed. Women with Stage IV breast carcinoma who were receiving cytotoxic chemotherapy (380 patients) or endocrine therapy (371 patients) and had at least 1 lytic bone lesion were given either pamidronate 90 mg as a 2-hour infusion monthly for 2 years or a placebo infusion. After the two studies were pooled, 367 patients treated with pamidronate and 384 patients given placebo were available for analysis. The median time to first complication (pathologic fracture, vertebral collapse, spinal cord compression, or treatment of bone with radiation or surgery) was 12.7 months for the pamidronate patients and 7.0 months for placebo patients (P = 0.001). The time to first fracture was 25.2 months for pamidronate patients and 12.8 months for placebo patients (P = 0.003). The proportion of patients with fracture was 40% for pamidronate vs. 52% for placebo (P = 0.002); the proportion with radiation administered to bone was 29% for pamidronate vs. 43% for placebo (P = 0.001); and the proportion with any skeletal event was 51% for pamidronate vs. 64% for placebo (P = 0.001). The skeletal morbidity rate (the number of complications per year) at 24 months was 2.4 for the pamidronate group and 3.7 for placebo (P = 0.001). Pain and analgesic use was decreased among the pamidronate patients. There was no difference in survival between the groups. Not all patients responded to the same dose of bisphosphonate. Recent data suggests that patients who have a normalization of their urinary excretion of N-telopeptide have a reduced risk of progression of disease in bone and fracture. In summary, the addition of pamidronate to standard chemotherapy or endocrine therapy produces a sustained reduction in skeletal complications in breast carcinoma patients with osteolytic bone metastases.